The benzodiazepine antagonist, Ro 15-1788 does not decrease ethanol withdrawal convulsions in rats. - Little, H; Taylor, S; Nutt, D; Cowen, P (1985)
The effects of the benzodiazepine antagonist, Ro 15-1788 on ethanol withdrawal convulsions were investigated in rats. The study originated from recent reports of benzodiazepine binding activity in urine of alcoholics during withdrawal. No alleviation of convulsions was found with Ro 15-1788. This suggested that this component of the withdrawal syndrome is not due to endogenous production of a benzodiazepine inverse agonist (contragonist), as Ro 15-1788 prevents the action of this type of compound.